Dampak Transisi SAK EP terhadap Profitabilitas Bank Perekonomian Rakyat (BPR) di Bali - Ni Wayan Lady Andini; Ni Kadek Cahya Dwi Utami; Ni Putu Yeni Ari Yastini; I Wayan Adnyana (Jurnal Ilmiah Raflesia Akuntansi, 2026)
The Rural Bank (Bank Perekonomian Rakyat or BPR) industry plays a vital role in regional economic development, particularly in Bali which is dominated by the MSME sector. The Financial Services Authority (OJK) mandates BPRs to transition from SAK ETAP to SAK EP effective January 1, 2025. This regulatory shift fundamentally alters the credit loss measurement from an incurred loss model (PPAP) to a forward-looking expected credit loss model (CKPN). This study empirically examines the impact of the SAK EP transition on the profitability (Return on Assets) of BPRs in Bali. Using an explanatory quantitative approach with a pre-post comparison design, the research analyzed the annual financial statements of 44 BPRs with total assets exceeding Rp100 Billion for the years 2024 and 2025. Following a Shapiro-Wilk normality test which confirmed normal data distribution, a Paired-Samples T-Test was conducted. The results demonstrated a significant difference in profitability before and after the SAK EP implementation (Sig. 0.025 < 0.05). The average profitability notably increased from 1.82% to 2.07% post-transition. Although higher provisioning (CKPN) theoretically suppresses earnings, BPRs successfully mitigated this impact through conservative credit practices and localized risk management. Aligning with Institutional Theory, complying with coercive regulatory pressures not only granted institutional legitimacy but ultimately strengthened the banks' long-term business sustainability.